HUBUNGAN ANTARA FOLLOWERSHIP STYLES DAN WORK EFFICACY PADA KARYAWAN INDUSTRI PENERBANGAN - Kindangen, Ivana Alessandra; Budiarto, Yohanes (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
PT. X is one of the largest aviation companies in Indonesia that provides both domestic and international flight services and has been in operation for approximately seven decades. In facing the competitive challenges, PT. X must recognize that the company's success does not solely depend on technology and infrastructure, but also on the quality of human resources, especially in terms of work effectiveness. To improve work effectiveness, it is crucial for each employee to have occupational self-efficacy, or what is referred to as work efficacy in the work life (Fullemann et al., 2015). Work efficacy is influenced not only by technical skills or individual work experience but also by environmental factors, work culture, and social relationships with peers and superiors. One such factor is followership styles. The purpose of this study is to explore the relationship between followership styles and work efficacy among employees in the aviation industry at PT. X. This study uses a quantitative method involving 152 active employees at PT. X. Data collection was carried out through the distribution of questionnaires. Two measurement tools were used: the Occupational Self-Efficacy Scale (OSS) by Rigotti (2008) and the Followership Styles Questionnaire (FSQ) by Kelley (19950. The results show that followership styles have a significant correlation with work efficacy. The followership style with the strongest correlation is the exemplary style (r = 0.755, p < 0.05), while the style with the weakest correlation is the passive style (r = 0.212, p < 0.05).